2011
DOI: 10.1021/ja2035128
|View full text |Cite
|
Sign up to set email alerts
|

Crowding Promotes the Switch from Hairpin to Pseudoknot Conformation in Human Telomerase RNA

Abstract: Formation of a pseudoknot (PK) in the conserved RNA core domain in the ribonucleoprotein human telomerase is required for function. In vitro experiments show that the PK is in equilibrium with an extended hairpin (HP) structure. We use molecular simulations of a coarse-grained model, which reproduces most of the salient features of the experimental melting profiles of PK and HP, to show that crowding enhances the stability of PK relative to HP in the wild type and in a mutant associated with dyskeratosis conge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(116 citation statements)
references
References 30 publications
7
108
1
Order By: Relevance
“…We chose this pseudoknot because it has two fairly long stems containing six and nine Watson-Crick base pairs. We had previously conducted simulations of the two stems at 15 • C in the limit of high ionic strength 25 and found that, for k r = 1.4 Å −2 and k φ = 4 rad −2 , the time averages of (r − r 0 ) 2 , (φ 1 − φ 1,0 ) 2 and (φ 2 − φ 2,0 ) 2 agreed well with the standard deviations computed from the NMR structure. The time averages were not very sensitive to a specific choice of U 0 ST .…”
Section: Stacking Interactionssupporting
confidence: 60%
“…We chose this pseudoknot because it has two fairly long stems containing six and nine Watson-Crick base pairs. We had previously conducted simulations of the two stems at 15 • C in the limit of high ionic strength 25 and found that, for k r = 1.4 Å −2 and k φ = 4 rad −2 , the time averages of (r − r 0 ) 2 , (φ 1 − φ 1,0 ) 2 and (φ 2 − φ 2,0 ) 2 agreed well with the standard deviations computed from the NMR structure. The time averages were not very sensitive to a specific choice of U 0 ST .…”
Section: Stacking Interactionssupporting
confidence: 60%
“…Such extensions can include biopolymers in aqueous solutions, such as unfolded proteins, whose persistence lengths can be sensitive to excluded-volume interactions [6], and whose uncrowded size distributions can be independently computed [13]. For a single biopolymer in a crowded environment, our computational methods can be directly applied, given as input the requisite shape distribution [18,19,83]. Simulating solutions of multiple selfavoiding polymers would require incorporating polymerpolymer interactions [68,84].…”
Section: Discussionmentioning
confidence: 99%
“…We use a variant of the coarse-grained SOP model (29,31), where each of the 176 residues in LZ26 is represented by a bead centered at the C α position (SI Text). The α-helical secondary structure is stabilized by interactions which mimic (i, i + 4) hydrogen bonding (32). We use residuedependent energies for tertiary interactions (30).…”
Section: Methodsmentioning
confidence: 99%